2010
DOI: 10.1371/journal.pone.0010630
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNA-21 as a Biomarker for Chemoresistance and Clinical Outcome Following Adjuvant Therapy in Resectable Pancreatic Cancer

Abstract: BackgroundPancreatic ductal adenocarcinoma (PDAC) has a dismal prognosis. The high risk of recurrence following surgical resection provides the rationale for adjuvant therapy. However, only a subset of patients benefit from adjuvant therapy. Identification of molecular markers to predict treatment outcome is therefore warranted. The aim of the present study was to evaluate whether expression of novel candidate biomarkers, including microRNAs, can predict clinical outcome in PDAC patients treated with adjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
185
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(199 citation statements)
references
References 63 publications
10
185
2
2
Order By: Relevance
“…MiR-21 was up-regulated in pancreatic adenocarcinomas in this and other studies and has been related to short survival. 20,22,38,39 Increased miR-21 expression increases the proliferative and invasive potential in several types of cancer, it has anti-apoptotic and pro-angiogenesis properties and its expression may represent an adaptation to a hypoxic environment that favors cancer cell survival. 40 In accordance with others, we found that miR-148a, miR-216b and miR-217b were some of the miRNAs with the most significantly decreased expression in pancreatic adenocarcinomas compared with chronic pancreatitis and normal pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-21 was up-regulated in pancreatic adenocarcinomas in this and other studies and has been related to short survival. 20,22,38,39 Increased miR-21 expression increases the proliferative and invasive potential in several types of cancer, it has anti-apoptotic and pro-angiogenesis properties and its expression may represent an adaptation to a hypoxic environment that favors cancer cell survival. 40 In accordance with others, we found that miR-148a, miR-216b and miR-217b were some of the miRNAs with the most significantly decreased expression in pancreatic adenocarcinomas compared with chronic pancreatitis and normal pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…High priority must be given to understanding the mechanisms of occurrence and development of pancreatic cancer and identifying novel diagnostics and effective therapeutics (10,11). MiR-141 is a member of the miR-200 family that mainly affects the epithelial-mesenchymal transition (EMT) process (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [44] showed that overexpression of miR-21 was correlated with disease progression and poor prognosis in breast cancer. Recently, Hwang et al [45] investigated whether miR-21 can predict clinical outcome in pancreatic ductal adenocarcinoma (PDAC) patients treated with adjuvant therapy. The results suggested that low miR-21 expression was seen by adjuvant treatment in PDAC patients and anti-miR-21 increased anticancer drug activity in vitro.…”
Section: Discussionmentioning
confidence: 99%